Time for a New Norm: Experiences of ‘Being Informed’ and ‘Having Choice’ for Prenatal Screening for Chromosomal Conditions: A Qualitative Study - Niamh Ireland‐Blake; Fiona Cram; Kevin Dew; Sondra Bacharach; Peter Stone; Jeanne Snelling; Christina Buchanan; Sara Filoche (Health Expectations, 2025)
ABSTRACT Background Participating in prenatal screening for chromosomal conditions is premised on an informed choice to accept or decline. Aim The aims of this paper are to describe people's experiences of informed choice and how these relate to the experience of prenatal screening. Method Thirty‐eight people were recruited and their experiences were explored through narrative enquiry, following an iterative and in‐depth reflexive analysis. Findings Informed choice meant ‘being informed’ in ways that met people's cultural needs, values and preferences (e.g., how much information and how it was communicated) and ‘having choice’ (e.g., choice about ‘being informed’, who was involved and choice to enact the decision). ‘Being informed’ affected ‘having choice’. Four themes describe experiences of how informed choice as an ethical principle was upheld: ‘All I knew it was something that should be done’, ‘Going in blind’, ‘It would have been frowned upon’ and ‘I knew I could decline’. For example, the experience of ‘I knew I could decline’ describes how the ethical principle of ‘informed choice’ was fully realised. There was a choice about how information was shared that meant people gained knowledge about prenatal screening and a choice about who was involved in this process. A relational experience for ‘being informed’ (e.g., with their pregnancy carer and the decision‐makers) was upheld. People knew that they would be fully supported in enacting their decision. These experiences were not common. Conclusions In the absence of ‘being informed’, the possibility for ‘having choice’ is eroded. ‘Having choice’ requires people to have information so that it meets their needs, values and preferences to make sense of it as it relates to their values for decision‐making. Considering ‘being informed’ as an epistemic justice obligation would mitigate eroding the possibility of ‘having choice’. For example, when people experienced prenatal screening as ‘I knew I could decline’, it was an epistemically just experience as all the elements for ‘being informed’ for them were met and the relational experience upheld ‘having choice’. The challenge remains for this to be the experience for everyone considering prenatal screening, not just in Aotearoa but globally. Patient or Public Contribution The interview questions were reviewed through group discussion with eight people who had lived experiences of prenatal screening for chromosomal conditions. The research was also informed by a researcher who had no lived experience of the screening service as a counter‐view. The premise of this study is to highlight how women and pregnant people experience the consenting process for prenatal screening. The findings may inform organisations, researchers and practitioners about developing approaches for better enabling informed choice in future practice.